Evaluation of the Endothelial Cell Density and the Central Corneal Thickness in Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma - Bożydar T. Tomaszewski; Renata Zalewska; Zofia Mariak (Journal of Ophthalmology)
Purpose. Evaluation of central corneal thickness (CCT) and endothelial cell density (ECD) in patients with senile cataract and coexisting pseudoexfoliation (PEX) syndrome with glaucoma (PEXG) and without glaucoma using specular microscopy. Participants and Methods. The study included 122 patients (217 eyes). In this group of patients we identified 133 eyes with PEX syndrome (65 with glaucoma, 68 without glaucoma) and 84 eyes without PEX syndrome. ECD and CCT were measured in each eye by specular microscopy. Results. ECD in eyes with PEX syndrome without glaucoma (2297 ± 359 cell/mm2) and in eyes with PEXG (2241 ± 363 cell/mm2) was lower than in the control group (2503 ± 262 cell/mm2) (P<0.001). CCT in eyes with PEXG (508.2 ± 32.6 μm) was thinner than in eyes with PEX syndrome without glaucoma (529.7 ± 30.3 μm) and control group (527.7 ± 29.4 μm) (P<0.001). Conclusions. This research shows that in eyes with PEX syndrome, both with and without glaucoma, ECD was statistically significantly lower than in the control group. In patients with PEXG, CCT was statistically significantly thinner than in the PEX syndrome and control group.